Concomitant primary peritonitis, septic shock and empyema thoracis in a young girl: a rare case report - Singh, Scott Arockia; Jeyasekharan, D. Devaprasath; Jeyasekharan, S. Sabu; Vidhyasagar, P. Bala; Nithila, C.; Devaprasath, Renu; Perumal, S. Nishal; Chandrika, Katla Vishnu (International Surgery Journal, 2019)
Primary peritonitis is a condition in which there is no intraabdominal source of infection demonstrated during laparotomy. It is uncommon and can affect any age group from childhood to the elderly. We report here a case of Primary peritonitis with septic shock as a presenting feature, associated with empyema thoracis. This combination was not reported previously in the literature. Our patient was a 15-yr old girl with a ten day history of fever, cough, dyspnea, abdominal pain and loose stools initially treated elsewhere. She was brought to the emergency in a gasping state, bradycardia, hypotension, tachypnoea and a distended abdomen. She was intubated, resuscitated and a bedside ultrasound revealed free fluid present all over peritoneal cavity. Emergency laparotomy under general anesthesia showed extensive thick yellow coloured nonfoul-smelling purulent fluid all over the peritoneal spaces with distended bowel loops. A thorough search confirmed no evidence of hollow-viscus perforation, peritoneal lavage, appendicectomy and laparostomy were done. Postoperatively she was ventilated electively and managed in a high dependency care unit with broad spectrum antibiotics and respiratory supportive measures. However she continued to have high fever, tachycardia, tachypneic and developed left massive pyothorax. Thoracoscopic drainage of the flakes of pus in the pleural cavity with extensive decortication done. Then, once her sepsis was well controlled, underwent laparostomy closure. However, post laparostomy-closure had signs of LV dysfunction with respiratory failure and managed with cardiac drugs. She had a turbulent postoperative course, gradually recovered, and was discharged home after nine weeks of admission.